Ketidaksesuaian Barang Yang Dibeli Melalui E Commerce Ditinjau Dari Aspek Perlindungan Konsumen - Hasdiana Juwita Bintang (ARBITRASE: Journal of Economics and Accounting, 2022)
This study aims to describe the legal protection obtained by consumers for non-conformance of goods purchased through e-commerce, an overview of e-commerce in Indonesia, the provisions for purchasing goods through e-commerce according to laws and regulations in Indonesia, and how the legal protection for consumers for the nonconformity of goods purchased through e-commerce. The research method used is descriptive with a normative research type, the data collection method is carried out by means of a literature study, the analysis used is qualitative analysis. The brief description of the research is that the trading system used in e-commerce is designed to sign electronically. This electronic signature is made from the time of purchase, inspection and delivery. Therefore, the availability of correct and accurate information about consumers and companies in e-commerce is an absolute prerequisite.